1982
DOI: 10.1159/000233167
|View full text |Cite
|
Sign up to set email alerts
|

Dextran-Reactive Antibodies in Healthy Infants and Toddlers – Relation to Type of Feeding

Abstract: The appearance of dextran-reactive antibodies (DRA) during the first 2 years of life was studied in 88 healthy newborn babies in an effort to provide information about the origin of DRA in normal persons. The results were related to type of feeding, immunizations and to blood group of infants and their mothers. No DRA were detected in cord sera by passive hemagglutination. At 3 months of age 42% had DRA, at 8 months 95 % and at 27 months 84%. The latter figure corresponds to previous reports of DRA in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…In our previous investigation we showed that the levels of DRA were significantly higher at 8 months than at 2 years of age, which was the point of time for the last sampling in the study (2). The present follow-up study shows a further decrease in DRA titres from that age.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In our previous investigation we showed that the levels of DRA were significantly higher at 8 months than at 2 years of age, which was the point of time for the last sampling in the study (2). The present follow-up study shows a further decrease in DRA titres from that age.…”
Section: Discussionsupporting
confidence: 58%
“…Such high titres may rarely be associated with anaphylactoid reactions after infusion of clinical dextran (1). In a previous study we showed that DRA appeared early during infancy, with peak titres at approximately 8 months of age (2). The appearance of DRA was not influenced by immunization against diphtheria, tetanus and pertussis or by the maternal blood group.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…However, it is possible that these macromolecules could trigger the release of several vasoactive mediators including histamine, kinins, and products of the lipoxygenase pathway [17]. As dextran is a component of toothpaste, sucrose-containing foods, and some prescribed medications, many individuals can be shown to carry dextranreactive antibodies [ 18,191. Hedin and associates showed that patients who react to dextran have higher levels of dextran-reactive antibodies of the IgG class than do non-reactors, and that the severity of of DIARs correlated directly with the pre-exposure antibody level [16,20].…”
Section: Anaphylactoid Reactionsmentioning
confidence: 99%